Open Versus Endovascular Repair of Isolated Iliac Artery Aneurysms. (January 2019) - Zhorzel, Sven; Busch, Albert; Trenner, Matthias; Reutersberg, Benedikt; Salvermoser, Michael; Eckstein, Hans-Henning; Zimmermann, Alexander
Purpose: Outcomes of open iliac artery repair (OIR) and endovascular iliac artery repair (EVIR) were compared at a tertiary referral vascular center. Methods: From 2004 to 2015, all patients treated for isolated iliac artery aneurysms (IAAs) were retrospectively identified, and patient records and computed tomography (CT) scans were analyzed. The primary end point was overall survival; secondary end points were 30-day mortality and morbidity and freedom from reintervention. For follow-up, data from outpatient visits and CT scans following a standard surveillance protocol were used. Results: A total of 106 IAAs in 94 patients were treated (mean follow-up: 35.7 months; 66 OIR; 40 EVIR). Six (15%) aneurysms from the EVIR group and 4 (6.1%) from open-operated IAA presented in the state of rupture. There was no difference in overall survival between EVIR and OIR ( P = .14). In multivariable analysis, higher risk of death was associated with ruptured IAA (rIAA; hazard ratio [HR]: 40.44, 95% confidence interval [CI]: 2.05-796.18; P = .02) and coronary heart disease (HR: 11.07, 95% CI: 1.94-63.36; P < .01). The 30-day mortality was 1.9% overall (0% OIR, 5.0% EVIR, P = .27), but there were no differences between OIR and EVIR in 30-day morbidity ( P = .11). Freedom from reintervention was higher for OIR than for EVIR ( P < .01). In multivariable analysis, a higher reintervention rate was seen in EVIR (HR: 10.80, 95% CI: 2.20-53.01; P < .01) and in rIAA (HR: 12.02, 95% CI: 1.31-111.11; P = .03). Conclusion: Iliac artery aneurysmss can be safely and effectively treated by EVIR or OIR regarding 30-day morbidity, mortality, and long-term survival, although freedom from reintervention is significantly lower after EVIR.